Artistic Adaptation Of Seenku Tone: Musical Surrogates Vs. Vocal Music - McPherson, Laura; James, Lucas (My University, 2021)
The tonal nature of many African languages has long raised questions about musical expression and the relationship between language and music. The two main areas of inquiry have been the relationship between tone and melody in vocal music (tonal textsetting) and the role of tone in musical surrogate languages (e.g. talking drums). However, the degree of similarity between these two genres in terms of tonal adaptation has remained an open question. In this paper, we present a case study comparing the role of tone in two musical traditions from the Sambla ethnic group of Burkina Faso: vocal music and a balafon (xylophone) surrogate language. We show that the two have different systems of tone-note correspondence and level of phonological encoding, indicating that musical adaptation of tone is not monolithic. We suggest that these different systems of tonal adaptation may stem from functional, structural, and cultural differences between the two musical genres.
Keywords: HUMANITIES and RELIGION::Languages and linguistics::Other languages::African languages; Seenku tone; vocal music; Musical surrogates